Function of Akkermansia muciniphila in Obesity: Interactions With Lipid Metabolism, Immune Response and Gut Systems - Xu, Yu; Wang, Ning; Tan, Hor-Yue; Li, Sha; Zhang, Cheng; Feng, Yibin (Frontiers in Microbiology, 2020)
Obesity and its metabolic syndrome, including liver disorders and type 2 diabetes, are a worldwide epidemic and are intimately linked to diet. The gut microbiota interaction has been pointed to as a hot topic of research in the treatment of obesity and related metabolic diseases by influencing energy metabolism and the immune system. In terms of the novel beneficial microbes identified, Akkermansia muciniphila (A. muciniphila) colonizes the mucosa layer of the gut and modulates basal metabolism. A. muciniphila is consistently correlated with obesity. The causal beneficial impact of A. muciniphila treatment on obesity is coming to light, having been proved by a variety of animal models and human studies. A. muciniphila has been characterized as a beneficial player in body metabolism and has great prospects for treatments of the metabolic disorders associated with obesity, as well as being considered for next-generation therapeutic agents. This paper aimed to investigate the basic mechanism underlying the relation of A. muciniphila to obesity and its host interactions, as identified in recent discoveries, facilitating the establishment of the causal relationship in A. muciniphila-associated therapeutic supplement in humans.